2015
DOI: 10.1002/advs.201500169
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Electronic Skin

Abstract: The skin is the largest organ of the human body and can sense pressure, temperature, and other complex environmental stimuli or conditions. The mimicry of human skin's sensory ability via electronics is a topic of innovative research that could find broad applications in robotics, artificial intelligence, and human–machine interfaces, all of which promote the development of electronic skin (e‐skin). To imitate tactile sensing via e‐skins, flexible and stretchable pressure sensor arrays are constructed based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
556
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 855 publications
(557 citation statements)
references
References 214 publications
(224 reference statements)
0
556
0
1
Order By: Relevance
“…A wide range of different material platforms including carbon-based nanostructures123 or organic compounds456, metals78 and oxides9 are currently investigated to realize devices that would be key to several emerging applications often related to the interface between humans and communication and information technology. Examples are wearable electronic transducers and processors or electronic energy harvesting systems as employed in electronic skin1011121314, implantable bioelectronic devices151617 or electronic textiles7. Progress in flexible electronics relies on the development of electronic materials and devices resistant to mechanical deformation.…”
mentioning
confidence: 99%
“…A wide range of different material platforms including carbon-based nanostructures123 or organic compounds456, metals78 and oxides9 are currently investigated to realize devices that would be key to several emerging applications often related to the interface between humans and communication and information technology. Examples are wearable electronic transducers and processors or electronic energy harvesting systems as employed in electronic skin1011121314, implantable bioelectronic devices151617 or electronic textiles7. Progress in flexible electronics relies on the development of electronic materials and devices resistant to mechanical deformation.…”
mentioning
confidence: 99%
“…To fulfill these demands, a broad range of materials, fabrication processes, and structural designs of the tactile sensor have been developed, [8] while sensing principles are mainly classified as either resistive [9][10][11] or capacitive types. [12][13][14] Many of resistive sensors use nanomaterial-embedded composites and exploit changes in contact resistance between the nanomaterials in the composite matrix (such as elastomer) under pressure loading, showing improved pressure sensitivity and mechanical flexibility compared to silicon-or metal-based piezoresistive sensors.…”
mentioning
confidence: 99%
“…Among these approaches, vibration energy harvesters (VEHs) receive majority of research interests and have been demonstrated by using one of piezoelectric39404142, electrostatic43444546, electromagnetic474849505152 and triboelectric5354555657 mechanisms. In addition to self-powered piezoelectric sensors, there are some self-powered triboelectric sensors reported to detect force, pressure, tactile, displacement, vibration, liquid volume, liquid flow, ion concentration, and organic concentration, etc585960616263646566676869. General speaking, when two triboelectrically opposite materials come in contact, they generate equal and opposite charges according to their place in the triboelectric series.…”
mentioning
confidence: 99%